2015
DOI: 10.1007/s10865-015-9645-2
|View full text |Cite
|
Sign up to set email alerts
|

Perceived ethnic discrimination and cigarette smoking: examining the moderating effects of race/ethnicity and gender in a sample of Black and Latino urban adults

Abstract: Perceived ethnic discrimination has been associated with cigarette smoking in US adults in the majority of studies, but gaps in understanding remain. It is unclear if the association of discrimination to smoking is a function of lifetime or recent exposure to discrimination. Some sociodemographic and mood-related risk factors may confound the relationship of discrimination to smoking. Gender and race/ethnicity differences in this relationship have been understudied. This study examines the relationship of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 43 publications
2
49
1
Order By: Relevance
“…39 Recent experience of discrimination increases risk of smoking among Black men, but not Black women. 63 Similar gender differences in the effects of discrimination are reported for other domains of psychopathology including psychological distress, 37 depressive and anxiety symptoms, 23,24 and major depressive disorder. 61 All these findings collectively suggest that Black males are the most likely victims of discrimination, and a significant proportion of psychopathology in Black males can be attributed to discrimination.…”
Section: Discussionmentioning
confidence: 59%
“…39 Recent experience of discrimination increases risk of smoking among Black men, but not Black women. 63 Similar gender differences in the effects of discrimination are reported for other domains of psychopathology including psychological distress, 37 depressive and anxiety symptoms, 23,24 and major depressive disorder. 61 All these findings collectively suggest that Black males are the most likely victims of discrimination, and a significant proportion of psychopathology in Black males can be attributed to discrimination.…”
Section: Discussionmentioning
confidence: 59%
“…Although the SRE is a commonly used and valid measure (Williams & Mohammed, 2009), future studies should examine reports of discrimination over differing time frames (e.g., lifetime versus year) as well as repeated measures over time (e.g., Peterson et al, 2016). A recent study by Brondolo and colleagues (2015) found that both past week and lifetime reports of discrimination predicted smoking behaviors among Black adults. However, after controlling for gender, the effects on current smoking status were stronger for the past week reports.…”
Section: Discussionmentioning
confidence: 98%
“…The enhanced burden of cumulative experiences of racial discrimination among Blacks may exacerbate the negative experience of race-based social exclusion (Goodwin et al, 2010; Stock et al, 2015). Several researchers have proposed that frequent experiences of discrimination can take a cumulative toll and result in negative health consequences (e.g., Brondolo et al, 2015, Williams & Mohammad, 2009). Longitudinal research with Black young adults has shown that cumulative experiences of racial discrimination predict an increase in substance use and risky sex (Gerrard et al, 2012; Stock et al, 2013).…”
Section: Does Past Discrimination Moderate the Effects Of Lab-based Dmentioning
confidence: 99%
“…In addition to these hypotheses, three-way interactions between acculturation/enculturation domains, family accusations of assimilation, and gender were explored in relation to alcohol use severity. These analyses were conducted based on differential gender effects of cultural stressors on substance use (Brondolo et al, 2015), differential gender effects of acculturation on alcohol use (Caetano & Clark, 2003), and gender differences in alcohol consumption (Eaton et al, 2012). …”
Section: Present Studymentioning
confidence: 99%